THE RELIGION-DEVELOPMENT DOMAIN OF WAHANA VISI INDONESIA CONCERNING CHILD EDUCATION IN ALOR – EAST NUSA TENGGARA - Ismoyo, Petsy Jessy (Universitas Kristen Satya Wacana, 2021)
This study tries to explain the role of faith-based organizations in achieving Sustainable Development Goals (SDGs) in Indonesia by showing the role of Wahana Visi Indonesia in education. Claiming themselves as Christian Faith-Based Organization that works according to the Christian Faith (Iman Kristen), WVI has huge impact on the sustainable development in Indonesia, including the education. By focusing this study to the case of Wahana Visi Indonesia (WVI), author aims to explain profoundly the effect religious actor has in development, particularly child education in Alor – East Nusa Tenggara. This study uses qualitative methods and literature study as an approach, in which authors did one-on-one interview as data collection technique, and examine through critical analysis to develop initial understanding in specified areas: religion and development and education. On the ground of major role of WVI as faith-based organization in the issue of SDGs, the author will discuss it accordingly in two main analysis as follows, the nexus of faith and development in Wahana Visi Indonesia in education field. Secondly, the author will examine the encounter and engagement that happened between religious actors (national and international), International Organizations, religious-affiliated schools and churches to understand how FBO operates in international development to achieve more effective and efficient in developing advocacy within religious-civil-society in Indonesia. Final result showed that religious is transformational, seen from the dynamic in three levels (macro-level, meso-level, micro-level) which outlined the progress of Wahana Visi Indonesia in intensifying child education in Alor – East Nusa Tenggara. The study concludes that Wahana Visi Indonesia as Faith-Based Organizations has successfully aligned ‘Christian Faith’ without the aim of proselytization in the realm of Child Education, as it works as catalyst of development for which it has influenced people-centered development regarding child education. It proves that WVI is catalyst to development, and study case of Alor – East Nusa Tenggara is an evidence how ‘faith’, ‘dialogue’ and ‘networks in religion-development domain’ has successfully made significant contribution in improving child education.